The dead of night - Marsden, John. (Boston : Houghton Mifflin Co., 1997)
Six determined Australian teenagers try to find their missing friends while continuing to resist the enemies who have invaded their country.
Originally published: Sydney : Pan Macmillan, 1994.
Sequel to: Tomorrow, when the war began.
Books for the Teen Age (NYPL).
Horn Book.
School Library Journal.
Young Adult
Keywords: Survival -- Fiction; War -- Fiction; Survival skills -- Fiction; War stories; Australia -- Fiction; Australia -- Fiction